Ploidy and recombination proficiency shape the evolutionary adaptation to constitutive DNA replication stress - Marco Fumasoni (Public Library of Science (PLoS), 2021)
In haploid budding yeast, evolutionary adaptation to constitutive DNA replication stress alters three genome maintenance modules: DNA replication, the DNA damage checkpoint, and sister chromatid cohesion. We asked how these trajectories depend on genomic features by comparing the adaptation in three strains: haploids, diploids, and recombination deficient haploids. In all three, adaptation happens within 1000 generations at rates that are correlated with the initial fitness defect of the ancestors. Mutations in individual genes are selected at different frequencies in populations with different genomic features, but the benefits these mutations confer are similar in the three strains, and combinations of these mutations reproduce the fitness gains of evolved populations. Despite the differences in the selected mutations, adaptation targets the same three functional modules in strains with different genomic features, revealing a common evolutionary response to constitutive DNA replication stress. Author summary Predicting the outcome of an evolutionary process requires precise knowledge of all the variables at play during adaptation. This goal is challenging to achieve since we often lack complete knowledge on which aspects of the organisms selected will influence their evolutionary response. Over the last decade, experiments in budding yeast have shown that the evolutionary adaptation induced by mutations that perturb important cellular processes can follow reproducible trajectories. We asked how genomic features influenced these trajectories by subjecting budding yeast strains with different features, such as ploidy and recombination proficiency, to the same mutation that imposes constitutive DNA replication stress. While we found many differences among the genes selected in different strains, we uncovered a general, feature-independent evolutionary trajectory which alters the same three cellular processes: DNA replication, the DNA damage checkpoint, and the linkage between sister chromosomes. Our results suggest that differences in genomic features control which genes adaptation modifies but have less effect on which biological processes are modified in response to genetic perturbations. We propose that this knowledge will increase our ability to predict similar adaptive processes outside the laboratory, including cancer progression, which is characterized by the somatic evolution of cells experiencing DNA replication stress.